THE INFLUENCE OF MENTAL HEALTH, EMOTIONAL INTELLIGENCE, AND LEADERSHIP ON EMPLOYEE PERFORMANCE - Bachmid, Franzezka Claire; Lina, Lina (Graduate Program of Universitas Tarumanagara, 2024)
The purpose of this research is to determine the influence of mental health, emotional intelligence, and leadership on employee performance at PT. XYZ. Researchers distributed questionnaires to all employees working at PT. XYZ with a sample size of 100 respondents. The research method used in this research is a quantitative research method using saturated sampling techniques. The data analysis method in this research uses Structural Equation Modeling (SEM), which is processed with SmartPLS 3.0 Software. The results of this research show that mental health, emotional intelligence, and leadership have a positive and significant effect on employee performance at PT. XYZ. The results of this research are expected to provide real benefits for employees at PT. XYZ, and this benefit is very important because it can solve various problems related to mental health, emotional intelligence and leadership on employee performance. Companies can take steps to improve mental health, such as providing mental health programs, work-life balance training, or psychological support resources. Companies can integrate emotional intelligence training in employee development programs to improve managerial and interpersonal skills. Companies must strive to pay special attention to developing leadership skills, either through training, mentoring, or leadership development programs so that they will improve overall employee performance.